ANALISIS REPRODUKSI KELINCI PERSILANGAN NEW ZEALAND WHITE DI KABUPATEN BLITAR - Zida Trisna Nianto; Edya Moelia Moeis; Agustina Widyasworo (AVES: Jurnal Ilmu Peternakan, 2019)
This research was conducted at UD. Sultoni partner farms in Blitar district. The purpose of this study was to determine factors that could support mastitis in UD. Sultoni partners. This research is expected to be an input for farmers to overcome mastitis. The research material uses UD. Sultoni partner dairy cows with a total of 64 eco-lactation dairy cows from partner farmes UD. Sultoni. The method used in this study is a survey through gathering interview information and observations from a sample. The results of this study indicate that there is a influence on the variables of milk production, age of cattle, floor cleanliness, and dipping on mastitis. Whereas the lactation month shows a positive influence of mastitis.